Brain Network Modularity During a Sustained Working-Memory Task - Moraschi, Marta; Mascali, Daniele; Tommasin, Silvia; Gili, Tommaso; Hassan, Ibrahim Eid; Fratini, Michela; DiNuzzo, Mauro; Wise, Richard G.; Mangia, Silvia; Macaluso, Emiliano; Giove, Federico (Frontiers in Physiology, 2020)
Spontaneous oscillations of the Blood Oxygenation Level-Dependent (BOLD) signal are spatially synchronized within specific brain networks and are thought to reflect synchronized brain activity. Networks are modulated by the performance of a task, even if the exact features and degree of such modulations are still elusive. The presence of networks showing anticorrelated fluctuations lend initially to suppose that a competitive relationship between default mode network and task positive networks supports the efficiency of brain processing. However, more recent results indicate that cooperative and competitive dynamics between networks coexist during task performance. In this study we used graph analysis to assess the functional relevance of the topological reorganization of brain networks ensuing the execution of a steady state working-memory (WM) task. Our results indicate that the performance of an auditory WM task is associated with a switching between different topological configurations of several regions of specific networks, including frontoparietal, ventral attention and dorsal attention areas, suggesting segregation of ventral attention regions in presence of increased overall integration. However, the correct execution of the task requires integration between components belonging to all the involved networks.